Quality Assessment Models in Public Transportation Services (International Journal of Scientific Research in Science and Technology, 2024)
Public authorities, transport agencies and private operators need to work together to continuously improve the performance of public transport. Any public transportation company must use a systemic survey-based approach that critically analyses client requirements in order to assess its success. Using the SERVQUAL model, an effort is made to gain a better knowledge of passenger attitude and satisfaction with the services offered by the public bus transportation system (MSRTC) in the model that is presented. The comparative cost benefit model is to find out the Ideal alternative with the highest Parameters (Benefit/Cost Ratio, NPV and IRR). In the presented model, an attempt is made to understand better alternative for investment with constant the level of passenger satisfaction towards services provided by the public bus Maharashtra State Road Transportation Corporation in India (MSRTC) and Private Bus Services in Maharashtra using comparative cost benefit model. In the presented last model, the methodology suggested that the decision making model helps us to know what facilities are to be put on priority for improvements. So, a decision making model is formulated for the two alternatives MSRTC (Maharashtra State Road Transport Corporation) and private bus services in which a decision factor is calculated based on the cost allotted to the particular facility and the negative response to that facility. This decision factor helps us to know which facility or parameter should be improved on priority which directly led to the improvement of services to increase the rate of customer satisfaction. In the presented model, the priority sequence to all the nine facilities is obtained for both the alternatives. Furthermore, the integrated framework of this study can enhance public transport performance and give customer satisfaction.